Atom species energy dependence on magnetic configurations in the perovskite yttrium orthoferrite - A. V. Baglov; L S. Khoroshko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The article represents the results of studying of the influence of atom species in the perovskite multiferroic yttrium orthoferrite YFeO3 on magnetic configurations by ab-initio methods. Four magnetic configurations possible in magnetic sublattice that were formed by iron atoms were analyzed. It is shown that different magnetic orderings change the lattice parameters and the ions occupied positions while preserving symmetry of the unit cell, the lowest state responds G-AFM type magnetic ordering. The lattice parameters are in good relevant published experimental data. The atom species energy dependence shows that the main role in magnetic properties goes to iron and oxygen. In the ground state, magnetic properties relate with Dzyaloshinskii – Moriya interaction, while in other configurations, these relate with superexchange through Fe- O-Fe chains. Obtained results are useful for analyzing and designing straintronics devices. Also, the results can be interesting for interpretation and predicting magnetic properties of partially or fully substituted orthoferrites including substitution on rare-earth elements.